Patient satisfaction : evaluating nursing care for patients hospitalized with cancer in Tehran Teaching Hospitals, Iran - Mehrnoosh, Akhtari-Zavare; Abdullah, Mohd Yunus; Syed Hassan, Syed Tajuddin; Said, Salmiah; Mohammad, Kamali (Canadian Center of Science and Education (CCSE), 2010)
Patient satisfaction is used as an important indicator of quality care and is frequently included in healthcare planning and evaluation. A cross sectional study was conducted to examine the relationship between cancer patients' satisfaction with nursing care in order to assist nurses in defining more clearly their roles in 10 government teaching hospitals in Tehran, Iran. A proportional stratified sampling method was used and data were collected via face-to-face interviews based on a validated Patient Satisfaction Questionnaire (PSQ) within a 3 month period. A total of 384 cancer patients aged 14 years old and above was selected. The majority of respondents were males 201 (52.3%), age group 45-54 years 102 (26.4%); and with family monthly income US$200-500, 234 (60.9%). The highest number and percentage 375 (97.7%) of respondents were admitted at general room, and 204(54.0%) of them were admitted at teaching hospital B of The University of Medical Science. The findings revealed that a vast majority of these respondents (82.8%) were satisfied with the nursing care provided to them, while the others (17.2%) were not. There was a significant relationship between patients' satisfaction and University's hospital, types of treatment (P≤0.05). Also; the University's hospitals was the best predictor for level of satisfaction. This study found that most of the respondents were satisfied with the nursing care, though they suggested some improvements especially with respect to interpersonal relation. Further research is needed to study in-depth the socio-cultural and environment parameters relevant to patients' satisfaction of nursing care.